2012
DOI: 10.1128/jb.01996-12
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Cellular Stress by TolC-Dependent Efflux Pumps in Escherichia coli Indicated by BaeSR and CpxARP Activation of spy in Efflux Mutants

Abstract: Escherichia coli has nine inner membrane efflux pumps which complex with the outer membrane protein TolC and cognate membrane fusion proteins to form tripartite transperiplasmic pumps with diverse functions, including the expulsion of antibiotics. We recently observed that tolC mutants have elevated activities for three stress response regulators, MarA, SoxS, and Rob, and we suggested that TolC-dependent efflux is required to prevent the accumulation of stressful cellular metabolites. Here, we used spy::lacZ f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 64 publications
4
53
1
Order By: Relevance
“…Such regulation is not unprecedented. For example, a high level of spy gene expression requires that both the Cpx and the Bae stress responses be activated (44). Thus, E. coli is able to fine-tune transcription levels and cellular physiology based on environmental stimuli, the degree of stress-induced damage, and the specific stress responses that become activated.…”
Section: Discussionmentioning
confidence: 99%
“…Such regulation is not unprecedented. For example, a high level of spy gene expression requires that both the Cpx and the Bae stress responses be activated (44). Thus, E. coli is able to fine-tune transcription levels and cellular physiology based on environmental stimuli, the degree of stress-induced damage, and the specific stress responses that become activated.…”
Section: Discussionmentioning
confidence: 99%
“…These data support the hypothesis put forth here and by others that Cpx induction in these mutants is due to the accumulation of a specific metabolite that can be handled only by these efflux pumps. Toxic, Cpx-inducing metabolites likely also induce the Cpx response in other organisms, since it has been demonstrated in E. coli that the Cpx pathway is activated in a tolC mutant (84), and in Sinorhizobium meliloti, a symbiotic partner of the leguminous plant Medicago sativa, the absence of a functional TolC protein leads to an increased susceptibility to antimicrobial agents and to activation of the Cpx response (85). Surprisingly, we found that Cpx induction by diverse cues could be reversed in all cases by the addition of exogenous iron (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Tannins, secondary metabolites of plants, can also induce the expression of MdtABC via BaeSR (761). Of the BaeSR regulon, there is a spy gene encoding a periplasmic chaperone (Spy), which shows increased levels in TolC or pump mutants and requires BaeSR and CpxAR systems for full activation (762). The expression of MdtEF is positively regulated by two AraC family activators, YdeO and GadX (763)(764)(765), and is also stimulated by N-acetyl-D-glucosamine through catabolite activation (763) and overexpression of a small (85-nucleotide) noncoding DsrA RNA (766).…”
Section: E Coli Efflux Pumpsmentioning
confidence: 99%